Discovery Learning for Problem-Solving Ability and Self-Efficacy - Faoziyah, Nina; Virgianti, Elina; Setiawan, Doni (Program Magister Pendidikan Matematika, Pascasarjana, Universitas Pasundan in collaboration with Asosiasi Guru Matematika Indonesia (AGMI) and Indonesian Mathematics Educators' Society (IMES), 2024)
Mastering problem-solving skills and fostering self-efficacy are crucial for student success as they equip individuals with the confidence and adaptability needed to navigate challenges effectively both academically and in real-life situations. However, the problem-solving skills of students and their self-efficacy are still relatively low. This study aims to assess the effectiveness of implementing the discovery learning model in enhancing students' problem-solving skills and self-efficacy. This study uses a mixed-method approach with high school students from one of the schools in Purwakarta. The sample is made up of two classes, one of which uses discovery learning and the other of which uses traditional classroom methods. with instruments including problem solving ability test questions, self-efficacy questionnaires, observation sheets, and interviews. Data analysis is conducted using an independent sample t-test. The instruments used include tests and non-tests, namely problem solving tests, self-efficacy scale questionnaires, observation sheets, and interviews. The research discovered notable variances in the mathematical problem-solving skills and self-efficacy of students who engaged in discovery learning versus those who engaged in conventional learning. It found that students in the discovery learning group exhibited better problem-solving skills and higher self-efficacy. Additionally, the study revealed a positive correlation between students' mathematical problem-solving abilities and their self-efficacy.